Identification of types and aquatic plants coverage area in the Bandar Kayangan Lembah Sari Lake, Rumbai Pesisir Sub-Regency, Pekanbaru, Riau Province. - Lauura Hermala Yunita; Efawani '; Eddiwan ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Bandar Kayangan Lembah Sari Lake is a man-made lake that is used to store water for agricultural and tourism purposes. There are many aquatic plants present in the lake and to understand the types and coverage area of the aquatic plant, a study was conducted in March-April 2016. A purposive sampling method was applied in collecting the aquatic plant. The plants were then identified based on Van Steenis (1981). The map of Bandar Kayangan Lake was downloaded using Google Earth application and the aquatic plant coverage areas in each station were then measured as a basis to predict the plant coverage area in the lake. The aquatic plants found during this study consisted of 4 families and 4 species, they were Cyperus rotundus, Paspalum commersoni, Nymphaea sp., and Pandanus sp. The aquatic plants coverage in the Bandar Kayangan Lake was around 18% and it is categorized as rare. The area that is not covered by aquatic plant was around 82% (1,054.058 m2).Keyword : Bandar Kayangan Lembah Sari Lake, aquatic plant, coverage area.